Engineered Adipose Tissue Formation Enhanced by Basic Fibroblast Growth Factor and a Mechanically Stable Environment - Seung-Woo Cho; Kang Won Song; Jong Won Rhie; Moon Hyang Park; Cha Yong Choi; Byung-Soo Kim (Cell Transplantation, 2007)
Engineered adipose tissue can be used in plastic and reconstructive surgery to augment soft tissue lost due to mastectomy or lumpectomy. The three-dimensional space provided by a scaffold capable of withstanding in vivo compressive forces and neovascularization may promote engineered adipose tissue formation. The objective of this study was to determine whether voluminous adipose tissue can be engineered by combining a mechanically stable environment with basic fibroblast growth factor (bFGF). Mechanical support structures, fabricated from biodegradable synthetic polymers, were placed into subcutaneous pockets of athymic mice. Human preadipocytes, containing fibrin matrix, with (group 1) or without (group 2) bFGF were injected into the space created by the support structures. Additionally, human preadipocytes containing fibrin matrix, with (group 3) or without (group 4) bFGF, were injected into subcutaneous spaces without support structures. Six weeks after implantation, the original implant volume was approximately maintained in groups 1 and 2, whereas groups 3 and 4 showed significant implant shrinkage. Adipogenesis and angiogenesis were more extensive in the group 1 than any other group. The fraction of human nuclear antigen-positive adipocytes in the implant was highest in group 1. Mouse adipocyte-specific genes were also expressed in the implants, again at the highest levels in group 1. Implanted preadipocyte apoptosis was significantly reduced in the groups treated with bFGF (groups 1 and 3) as opposed to those without (groups 2 and 4). This study demonstrates that combining a mechanically stable environment with bFGF can promote voluminous adipose tissue regeneration. This adipogenesis was likely promoted by the mechanically stable three-dimensional space, enhanced neovascularization, implanted cell survival, and host adipogenic cell migration. The method described in this study could be useful to augment adipose tissue used in plastic and reconstructive surgery.